2016
DOI: 10.1016/j.nbd.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypoxia Inducible Factor 1 in Hyperglycemia-Exacerbated Blood-Brain Barrier Disruption in Ischemic Stroke

Abstract: Diabetes is a major stroke risk factor and is associated with poor functional recovery after stroke. Accumulating evidence indicates that the worsened outcomes may be due to hyperglycemia-induced cerebral vascular complications, especially disruption of the blood-brain barrier (BBB). The present study tested a hypothesis that the activation of hypoxia inducible factor-1 (HIF-1) was involved in hyperglycemia-aggravated BBB disruption in an ischemic stroke model. Non-diabetic control and Streptozotocin-induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 85 publications
1
41
0
1
Order By: Relevance
“…HIF-1α upregulation after diabetic stroke has also been seen to play a role in the breakdown of the BBB. Knockout of HIF-1α ameliorated BBB permeability as well as tight junction disruption (263). A downstream target of HIF-1 is VEGF.…”
Section: Cerebrovascular Integritymentioning
confidence: 99%
“…HIF-1α upregulation after diabetic stroke has also been seen to play a role in the breakdown of the BBB. Knockout of HIF-1α ameliorated BBB permeability as well as tight junction disruption (263). A downstream target of HIF-1 is VEGF.…”
Section: Cerebrovascular Integritymentioning
confidence: 99%
“…In contrast, the therapeutic efficacy of MIL infusion with and without intravenous sedation in patients following SAH has been established in several clinical settings including SAH . Thus, the timing, severity, and sustainability of HIF‐1α upregulation and its downstream transcriptional effects may also be pursued in translational studies using genetically modified mice to identify more promising preventive or prophylactic interventions against post‐SAH DCI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several in vitro studies using a rat model reported discrepant findings, which indicated that HIF inhibition per se has been associated with improved blood-brain barrier 34,35 In contrast, the therapeutic efficacy of MIL infusion with and without intravenous sedation in patients following SAH has been established in several clinical settings including SAH. 6,11,14,[29][30][31][32][33] Thus, the timing, severity, and sustainability of HIF-1α upregulation and its downstream transcriptional effects may also be pursued in translational studies using genetically modified mice [36][37][38] to identify more promising preventive or prophylactic interventions against post-SAH DCI.…”
Section: Discussionmentioning
confidence: 99%
“…High blood glucose levels are associated with both degree of disability and infarct size in human and in rodent models of stroke [3, 17, 24]. Diabetes enhances the development of stroke and neuronal destruction by activating cortical apoptotic activity following cerebral ischemia [17, 34, 35]. Diabetes aggravates cerebral stroke and its poor outcomes after focal cerebral ischemia [17, 24].…”
mentioning
confidence: 99%
“…Thus, hyperglycemia is accepted as risk factors that appear to perform critical roles in the severity of stroke. Hyperglycemia aggravates cerebral damage, increases morbidity and mortality, and worse clinical outcomes [4, 20, 34, 35]. Inflammation response is one of the pathological mechanisms in diabetes mellitus.…”
mentioning
confidence: 99%